(untitled) (Global Journal of Medical Research, 2019)
The liver is the multi-functional and vital organ of the body. It is found in the upper abdomen region of the vertebrates. Due to long-term damage, liver stops functioning properly which may lead to cirrhosis. This long-term damage occurred when scar tissue replaces the normal tissue of the liver. This disease develops slowly and has no early symptoms, but when it develops and become worse, then it leads to tiredness, itchiness, weakness, yellow skin, swelling in the lower legs, spider-like blood vessels and an easy bruise on the skin with fluid in the abdomen. The severe complications like bleeding dilated veins in esophagus or stomach, hepatic encephalopathy leading to confusion and unconsciousness and liver cancer may occur in the body. This review article is focusing on the effect of liver damage in the human body.